INTEREST OF VOCATIONAL HIGH SCHOOL STUDENTS IN ENTREPRENEURSHIP IN AGRICULTURE - Hendra; Zulkarnain Lubis; Endang Sari Simanullang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to find out what factors influence the interest of vocational high school students to become entrepreneurs in the agricultural sector. This study was located at SMK Negeri 2 Lima Puluh, Batu Bara Regency, North Sumatra. In this study, the author used a quantitative approach. The quantitative approach is the measurement of quantitative data and objective statistics through scientific calculations. In this study, the population was all vocational students of plantation crop agribusiness totaling 75 people. The sampling technique used saturated sampling where all populations were sampled from classes X, XI and XII. The data analysis method used in this study was SEM-PLS analysis. The results of this study were talent influencing entrepreneurial interest. The courage to take risks influenced entrepreneurial interest. Capital did not influence entrepreneurial interest. Opportunities did not influence entrepreneurial interest. Business experience did not influence entrepreneurial interest. Parental and environmental participation did not influence entrepreneurial interest.